2015
DOI: 10.1111/apt.13244
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D level is associated with disease severity and response to ursodeoxycholic acid in primary biliary cirrhosis

Abstract: SUMMARY BackgroundSerum vitamin D levels are associated with bone complications in patients with primary biliary cirrhosis (PBC). Increasing evidence suggests a nonskeletal role of vitamin D in various autoimmune and liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 44 publications
2
47
1
Order By: Relevance
“…These findings are in contrast to a recent publication demonstrating that 25(OH)D concentrations were significantly associated with response to UDCA among patients with primary biliary cirrhosis, with lower concentrations of 25(OH)D observed in non-responders(40). The different study population and endpoints employed in that study may account for the contrasting results observed herein, as the primary findings of the UDCA trial revealed overall effect of the intervention on recurrent adenomas.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in contrast to a recent publication demonstrating that 25(OH)D concentrations were significantly associated with response to UDCA among patients with primary biliary cirrhosis, with lower concentrations of 25(OH)D observed in non-responders(40). The different study population and endpoints employed in that study may account for the contrasting results observed herein, as the primary findings of the UDCA trial revealed overall effect of the intervention on recurrent adenomas.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with PBC normally suffer from itching and fatigue, regardless of disease severity[14,37,38]. Serum fat-soluble vitamin D deficiency may be detected, particularly in advanced PBC patients[39,40]. Metabolic bone disease includes osteoporosis and, more rarely, osteomalacia, which have been considered important complications of PBC[41,42].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Malabsorption, steatorrhea, and fat-soluble vitamin D deficiency are uncommon, except in cases of advanced liver disease and long-standing, severe cholestasis[9,10,39,40,43]. In addition to vitamin D deficiency, as luminal bile acid levels in severe cholestasis are below the critical concentration required for micelle formation and subsequent lipid absorption, clinically-relevant fat-soluble vitamin (vitamin A, E and K) deficiencies may also exist in PBC[43].…”
Section: Fat-soluble Vitamin Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Their encouraging data from an independent cohort gave our previous findings a quickly validation, and further proved that vitamin D status may be closely related to disease progression and therapy outcome in primary biliary cirrhosis (PBC). 1,2 As mentioned by Bruns et al, the relationship between vitamin D level and PBC may involve a prognostic associated symptom -fatigue, which is also connected with hypovitaminosis D. Although existing data are limited to prove this linkage, it will be interesting to see whether some special physical conditions caused by disease will affect vitamin D level, and whether changes in vitamin D have an effect on disease in turn.…”
mentioning
confidence: 96%